Value of combined Plasma NGAL, Cystatin C And NT-proBNP in the diagnosis of cardiorenal syndrome type 1. (14th October 2021) - Phan, H A O
Abstract: Background: The presence of acute kidney injury in the setting of acute heart failure (AHF) or acute decompensated heart failure (ADHF) is very common occurrence and was termed cardiorenal syndrome 1 (CRS1). Neutrophil gelatinase-associated lipocalin (NGAL) in the blood and urine is one of the earliest biomarkers of acute kidney injury due to ischemia or renal toxicity. Cystatin C is early marker of renal dysfunction. NT-proBNP is valuable in the diagnosis, prognosis and treatment of acute and chronic heart failure. This study was aimed to evaluate the diagnostic efficacy of the combination of plasma NGAL, Cystatin C and NT-proBNP in diagnosis of CRS1. Methods: There were 139 patients with AHF or ADHF in the department of Cardiovascular resuscitation and Interventional cardiology at Ho Chi Minh City 115 People Hospital from November 2018 to May 2019. This was a prospective cohort study. Results: There were 48 cases (rate 34.5%) with CRS1, mean age 66.12±15.77, men accounted for 50.4%. There were no significant differences of vital signs on admission, diagnosis, type of heart failure between CRS1 and Non-CRS1 groups. The urea, creatinin on first day (creatininD1) and third day (creatininD3), NT-proBNP, Cystatin C, NGAL levels were higher in the group with CRS1 than Non-CRS1, the difference was statistically significant p<0.05. The optimal cut-off NGAL for diagnosing CRS1 was >353.23 ng/ml, Area Under Curve (AUC) was 0.732 (95% CI 0.65–0.80, p<0.001), sensitivity 74.47%, specificity 68.48%, positive predictive value 54.7%, negative predictive value 84%. The optimal cut-off Cystatin C for diagnosing CRS1 was >1.81 mg/dl, AUC was 0.787 (95% CI 0.71–0.85, p<0.001), sensitivity 75%, specificity 83.52%, positive predictive value 70.6%, negative predictive value 86.4%. The optimal cut-off NT-proBNP for diagnosing CRS1 was 17681 pg/ml, AUC was 0.683 (95% CI 0.59 – 0.76, p<0.001), sensitivity 53.19%, specificity 77.17%, positive predictive value 54.3%, negative predictive value 76.3%. Combined three biomarker plasma NGAL, Cystatin C and NTproBNP, the specificity of the diagnosis was the highest 95.6%, the positive predictive value was the highest 84.62% in diagnosing CRS1. Conclusions: The combined plasma NGAL, Cystatin C and NT-proBNP is high value in the diagnosis of CRS1 in patients with AHF or ADHF. Funding Acknowledgement: Type of funding sources: None.